Industrial Relations in the Digital Sharing Economy: A Critical Review of Labor Informalization and Social Partnership Relations - Fuat Edi Kurniawan (Deputy of Social Sciences and Humanities, the Indonesia Institute of Sciences (LIPI), 2020)
This study provides a critical analysis of digital transformation which not only creates new patterns in production, distribution, and consumption but also has implications for power. Various issues have yet to be responded to thoroughly by policymakers to have allowed the new labor relations created in the digital sharing economy to develop quickly and become fragile, especially for laborers. In this article used a qualitative method with the desk study approach, by collecting data and information through examinations, analyzing information data using secondary data. This data is in the form of books, journals, workforce data from BPS, supporting data from related institutions, laws and regulations related to work, reports and literature studies. The results of this study show the emergence of an online transportation based digital platform which has opened new job opportunities, on the other hand, the industrial relation formed are only based on